MOORA: Metode Sistem Pendukung Keputusan untuk Menentukan Kelayakan Peminjaman Modal Dana Bergulir - Evi Surya Ningsih; Havid Syafwan; Mhd Ihsan (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Koperasi Doni Jaya is one of the savings and loan cooperatives that provides solutions in assisting the provision and for various needs in a fast and easy loan process. However, the loan process takes a long time and must also determine the customer who is eligible to be given the capital loan. The model used to build this system is waterfall with stages of analysis, design, build & testing, and implementation. This research was carried out at the Koperasi Doni Jaya at the Asahan District Education Office. The Analysis phase is carried out to obtain the needs of the system that we developed with the MOORA method. The design phase is carried out to determine the interface design, and flowcharts on this system. Furthermore, the coding and testing stages are carried out to create a system and test using blackbox. Our findings are in the form of a decision support system to determine the feasibility of revolving fund capital lending. The test results show that this system is already running well, and is in accordance with the design, as well as the model applied. With this system, it can help this cooperatives determining eligible and uneligible customers to be given revolving fund capital loans.